The Characteristics of Historically Black College and University Presidents and Their Role in Grooming the Next Generation of Leaders. Issue 7 (July 2014) - Freeman, Sydney; Gasman, Marybeth
Background/Context: Although research on college and university presidents has grown in recent decades, historically Black college and university (HBCU) presidents have rarely been included in this research. We know almost nothing about the pathways to the HBCU presidency or the role that current presidents play in grooming future presidents. More literature is needed in order to deepen our understanding of the HBCU presidency. Purpose: With this study, we sought to capture the background characteristics of HBCU leaders, to lay the ground work for future studies on HBCU presidents, and to understand the role these leaders play in grooming and mentoring the next generation of HBCU leaders. Research Design: In order to answer our research questions, we used a combination a surveys, document analysis, and qualitative interviews. Conclusions and Recommendations: Our conclusions and recommendations point to a recycling of presidents at HBCUs as well as the disproportionate presence of long-term presidencies. Moreover, although grooming of future presidents is taking place, it is not systematic and would benefit from deeper thought and commitment.